Analisa Manajemen Risiko Pada Perusahaan Dagang Potong Ayam: Studi Kasus di PD Adil - Ai Solihat; Michael Abraham Siahaan; Alby Silmi Maulidan; Adiasa Tegar Prakoso; Muhammad Alfarisi Habibilah; Syti Sarah Maesaroh (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Chicken is a very popular and popular food source around the world. In addition to being delicious and nutritious, the way of livestock and cultivation are also relatively easy. Therefore, many chicken farming and chicken processing businesses were born, which of course are very promising to increase the pocket money pockets of entrepreneurs. Although it sounds easy and fun, in fact, the slaughter chicken processing business still often experiences risks that will hinder the business or even threaten the sustainability of the business. For example, market games, mafia in business, skyrocketing raw material prices, panic buying of the public, dishonest employees and others. The analysis of this research is the management of risk management in the chicken slaughter business of the PD Potong Adil company, where it has experience in managing chicken clocks with business twists and turns and ups and downs and competing in the market. Not only product risks but financial management risks to the risk of skyrocketing chicken prices in the market will also be discussed here. Our research method uses fishbone analysis, a fishbone-shaped diagram which is very easy for all circles to understand.